PENDAMPINGAN INISIASI USAHA SOUVENIR BERBASIS ECOPRINT MANGROVE BAGI PENGELOLA KAWASAN EKOWISATA DESA TAMBAKREJO, KABUPATEN MALANG - Pradipta, Naresvara; Prakosa, Galit Gatut; Muttaqin, Tatag; Triwanto, Joko; Kayanti, Mardita Riski; Ainiyah, Qurrotul; Anggara, Arik (Jurnal Abdi Masyarakat, 2024)
Ecotourism is a form of tourism that still pays attention to the preservation of unspoiled nature (ecology), maintaining social culture (Social), empowering local communities around the area (economic), and can provide learning and education to the community or visitors (education). If one of these aspects is missing, it is necessary to evaluate the ecotourism. Clungup Mangrove Conservation Tiga Warna (CMC Tiga Warna) is located in Tambakrejo Village, Sumbermanjing Wetan District, Malang Regency. The ecotourism area here is managed by the local Sendang Biru community who are members of the Bhakti Alam Sendang Biru Foundation. Socio-economic problems are one aspect that needs to be resolved in an effort to impact community welfare. This Community service provided by training in ecoprint production and assisting in digital marketing and advertising for CMC managers and agents to decrease the sosio-economic tension.